PERSPEKTIF HUKUM TERHADAP PERLINDUNGAN ANAK DAN LANJUT USIA - Wahyuni; Mubakkirah, Fadhliah; Khatimah, Andi Husnul (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2025)
Children and the elderly are categorized as vulnerable groups requiring special legal protection. Although the government has shown commitment to safeguarding the rights of children and the elderly, the practical implementation has yet to yield optimal outcomes. There is a pressing need for comprehensive legal regulations to ensure the effective protection of these groups, including the identification and regulation of specific areas of concern. This article explores the legal and institutional roles of the government, social welfare institutions (LKS), and the community in fulfilling the state’s obligation to protect children and the elderly. It also emphasizes the importance of legal frameworks that support adequate infrastructure, financial stimuli, budget allocation, and capacity development of social workers as key elements of protection. Furthermore, the article highlights that the legal responsibility to protect these vulnerable populations should be mainstreamed across all sectors of governance, and should not rest solely on a single social institution, in order to ensure a holistic and rights-based approach to protection.